Multibraided Fixed Retainers with Different Diameters after Magnetic Resonance Imaging (MRI): In Vitro Study Investigating Temperature Changes and Bonding Efficacy - Maria Francesca Sfondrini; Maurizio Pascadopoli; Paola Gandini; Lorenzo Preda; Domenico Sfondrini; Karin Bertino; Cinzia Rizzi; Andrea Scribante (MDPI AG, 2024)
Objectives: Orthodontists are often asked to remove fixed retainers before patients undergo magnetic resonance imaging (MRI). The present in vitro study was designed to analyze the heating and bonding efficacy of stainless steel multibraided fixed retainers after 1.5- and 3-tesla (T) MRI. Materials and methods: A total of 180 human mandibular incisors were used to create 45 specimens of four teeth each, divided into nine groups. Handmade multibraided fixed retainers of three different sizes, defined by the diameter of the initial wire used (0.008", 0.010" and 0.012"), were tested. Three groups underwent MRI at 1.5 T, another three groups underwent MRI at 3 T and the last three groups did not undergo MRI. Temperature was assessed before and after MRI. Shear bond strength (SBS) and adhesive remnant index (ARI) were assessed after MRI for all groups. Data were statistically analyzed (p < 0.05). Results: After 1.5 T exposure, no significant temperature increase from T0 to T1 was observed in any of the groups (p > 0.05). Regarding the 3 T groups, a significant difference from T0 to T1 was found for all the groups (p < 0.05). Temperature changes were not clinically relevant, as they were less than 1 °C for all groups except for group 3 (ΔT0-T1: 1.18 ± 0.3 °C) and group 6 (ΔT0-T1: 1.12 ± 0.37 °C). Furthermore, there were no significant differences between the temperature variations associated with different wire diameters (p > 0.05). Conclusions: No significant changes in SBS or ARI were found (p > 0.05). Clinical significance: Since overheating was irrelevant and adhesion values did not change, the tested devices were concluded to be safe for MRI examinations at 1.5 T and 3 T.